Self Assessment System, Pengetahuan, Dan Sanksi Pajak Berpengaruh Terhadap Kepatuhan Pajak Dengan Religiusitas Sebagai Variabel Moderasi - Utami, Amelia Febi; Andriani, Sri (Gorontalo Accounting Journal, 2024)
This study investigates the impact of several factors on taxpayer compliance, including understanding of the self-assessment system, knowledge of tax regulations, tax sanctions, and religiosity. The aim is to gain insights into what influences taxpayers to comply with tax regulations. The study employs quantitative data collection methods through surveys and questionnaires. Analytical techniques such as descriptive analysis, quality tests, classical assumption tests, and hypothesis testing are used. Results indicate that understanding of the self-assessment system, knowledge, and tax sanctions positively influence taxpayer compliance. Additionally, religiosity moderates the relationship between understanding the self-assessment system, knowledge, and taxpayer compliance, but not for tax sanctions.